Strategi Personal Branding Budiono Sukses sebagai Food Vlogger dalam Memperkuat Brand Image (Studi Kasus pada Akun YouTube Budiono Sukses) - Fadilah, Fahrian Rian; Setiadi, Tatak (The Commercium, 2025)
This research examines the personal branding strategy of Budiono Sukses (BS), a culinary vlogger, in building a strong brand image through the YouTube platform. Using a qualitative case study approach, the study identifies elements of personal branding, such as specialization in local culinary content, consistency in maintaining quality, and ethics in delivering reviews. Budiono specifically focuses on promoting traditional foods and small eateries that are often underexposed, thereby adding value to his content while reinforcing his identity as a culinary vlogger who supports the preservation of local culinary culture. The findings show that Budiono Sukses’s personal branding strategy successfully creates a close relationship between his audience, culinary business owners, and himself as a content creator. Through a consistent and authentic approach, Budiono has strengthened his brand image not only as a food reviewer but also as a connector who supports the existence of local culinary businesses in the digital space. This research highlights that well planned personal branding can serve as an effective tool to enhance the visibility of UMKM (Micro, Small and Medium Enterprises), expand their digital reach, and create a positive impact on preserving culinary culture in the modern era.